2005
DOI: 10.1073/pnas.0503524102
|View full text |Cite
|
Sign up to set email alerts
|

MAP-1 is a mitochondrial effector of Bax

Abstract: apoptosis ͉ mitochondria ͉ Bcl-2 family ͉ tumor suppressor

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
122
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(127 citation statements)
references
References 47 publications
(77 reference statements)
3
122
1
1
Order By: Relevance
“…29 It has been recently reported that an outer membrane mitochondrial protein, the modulator of apoptosis-1 (MAP-1), is a critical effector of Bax function. 30 Indeed, we show in this work that the association of Bax with mitochondria requires TOM22, a mitochondrial outer membrane protein. However, as stated by Newmeyer and Ferguson-Miller, 31 the latter observations are Figure 2 Bax interacts with TOM22.…”
Section: Discussionmentioning
confidence: 59%
“…29 It has been recently reported that an outer membrane mitochondrial protein, the modulator of apoptosis-1 (MAP-1), is a critical effector of Bax function. 30 Indeed, we show in this work that the association of Bax with mitochondria requires TOM22, a mitochondrial outer membrane protein. However, as stated by Newmeyer and Ferguson-Miller, 31 the latter observations are Figure 2 Bax interacts with TOM22.…”
Section: Discussionmentioning
confidence: 59%
“…This suggests a functional interaction between Bax and the CsAsensitive permeability transition pore complex (PTPC) (Marzo et al, 1998b;Belzacq et al, 2003). Another protein outside of the PTPC that may be required for Bax-mediated MOMP is the so-called modulator of apoptosis 1 (MAP-1) (Baksh et al, 2005;Tan et al, 2005).…”
Section: Mitochondrial Membrane Permeabilization: the Central Event Omentioning
confidence: 99%
“…MOAP-1 contains a BH3-like motif and is capable of triggering apoptosis in mammalian cells when overexpressed (10,11). Knocking down MOAP-1 by RNAi confers inhibition of apoptotic signaling triggered by multiple apoptotic stimuli and promotes anchorage-independent growth of tumor cells (11).…”
mentioning
confidence: 99%
“…MOAP-1 contains a BH3-like motif and is capable of triggering apoptosis in mammalian cells when overexpressed (10,11). Knocking down MOAP-1 by RNAi confers inhibition of apoptotic signaling triggered by multiple apoptotic stimuli and promotes anchorage-independent growth of tumor cells (11). Remarkably, isolated mitochondria from MOAP-1 knockdown cells were highly resistant to the cytochrome c (Cyto c)-releasing effect of recombinant Bax, suggesting that MOAP-1 may act as an effector for facilitating Bax function in mitochondria (11).…”
mentioning
confidence: 99%
See 1 more Smart Citation